Terno-de-reis e boi-de-mamão em Içara (SC): as relações dialógicas na linguagem folclórica do ciclo natalino num município multiétnico - Fernandes, Elza de Mello (2004)
This dissertation is in context of two folkloric manifestations of the Christmas cycle in Içara county (SC): terno-de-Reis and boi-de-mamão, in a dialogic perspective between the verbal and non-verbal languages (in this, with emplasis to constituent simbology of rituals) characteristics of this popular manifestations. We have taken as a goal the description of the communicative potential that these manifestations represent in Içara county (SC), selected for the present study throug the plurality of its ethnic constitution: Lusitanian-Azorian,Italian, Polish (the most evident in the county) and also the Indigenous and African2 substract. We proposed to explore the lead the research trough the analyses accomplished under three semiotic viewpoints: (i) the qualitative-iconic, (ii) the singular-indicative and (iii) the conventionalsymbolic, in the try to better describle what the affects are, which translate the symbologies of this fokloric manifestations in the socio-historic-cultural context of Içara. Therefore, we start from a socio-historic retrospective of the constitution and formation of these two manifestations of the Christmas cycle correlated to the Lusitanian-Azorian culture, with emphasis on the origin of the folklore (from the sacred to the profane) that covers the manifestations of the popular art